Research on Short-Circuit Current Calculation Method of Doubly-Fed Wind Turbines Considering Rotor Dynamic Process - Yin, Jun (Frontiers in Energy Research, 2021)
With the enlarging scale of doubly-fed induction generators (DFIGs) connected to power systems, it is important to analyze the influence of a short-circuit current to system relay protection. Due to the correct evaluation of the protection operation characteristics, the DFIG short-circuit current needs to be calculated accurately. But the current research on the short-circuit current of DFIG is based on the following assumption: the rotor excitation current is zero after the rotor crowbar is put, and the influence of its dynamic process is ignored. This will bring errors to the calculation results. This paper takes into account the influence of rotor current dynamics by studying the mechanism of the potential transient change of DFIG. The stator rotor flux linkage of DFIG in the event of a three-phase short-circuit is accurately calculated, and an improved RMS calculation method of doubly-fed wind turbine short circuit current is proposed. A physical experiment platform with an actual controller of a doubly-fed fan is established, based on RTDS. It can be seen from the experiment that the short-circuit current calculation method proposed in this paper is more accurate than those methods that ignore the rotor dynamic process. This study lays a foundation for further study of the influence of DFIG on the protection operation characteristics.